UJI EFEKTIVITAS ANTIINFLAMASI GEL EKSTRAK PINING BAWANG (Hornstedtia alliacea) PADA MENCIT (Mus musculus) YANG DIINDUKSI KARAGENAN 1% - Muhammad Khatami; Reza Farhan; Hafiz Hafiz (FORTE JOURNAL, 2022)
The purpose of this study was to determine the concentration of onion pining extract gel which has anti-inflammatory activity in carrageenan-induced male mice. Pining onion (Horstedtia alliacea) is a member of the ginger plant (Zingiberaceae) that grows in tropical areas including Halmanera. Pining onion is usually used as an energy supplier for hunting in the forest, treating wounds and infections, the seeds are consumed by children and adults. The benefit of this research is that this research can provide scientific and truthful information to the public regarding the anti-inflammatory effects of the pining onion plant, so that it can be used as an alternative inflammatory treatment. Pining onions contain flavonoid compounds, essential oils and several other compounds that are useful as anti-inflammatory. This study made three sample formulas with the active ingredient of pining onion extract with composition 0 (negative control), formula I 5%, formula II 10%, formula III 15% and diclofenac sodium (positive control) using the maceration method, with an interval of 30 minutes. for 8 repetitions of each suspension. Inhibition of edema in the FIII group (15% pining onion extract) had the same tendency as the K+ group (Na-Diclofenac). Meanwhile, at the lowest test dose the inhibition of edema was in the FI group (5% onion pining extract). The conclusion of this study is that administration of pining onion extract gel can show anti-inflammatory activity in carrageenan-induced mice. Pining onion extract gel at a concentration of 15% is the concentration that has the best anti-inflammatory activity compared to concentrations of 10% and 5%.